The future studies of women for Muslims - Ghalia, Bouhedda; Asar, AK (Global Business and Social Entrepreneurship Resources (GBSE), 2016)
There are many studies about women which have been done by Muslim scholars. The issue of women working outside home and holding public office positions is also still being debated by Muslim scholars nowadays- in fact it seems as a never ending issue in the Muslim world. Researchers have concluded in their research that a woman is permissible to work outside home as well as to hold any public office positions as long she follows Islāmic guidelines. In fact, a truly Islāmic society actually must comprise of women who join the working forces. A part of discussing those Islāmic guidelines; this paper also will highlight some future studies of women that scholars should focus in moving towards a better nation and Muslim civilization.